Circular Economy di Tingkat Desa: Pemberdayaan Karang Taruna dalam Pengelolaan Sampah Melalui Bank Sampah - Nurlinayanti, ⁠Leni; Nugroho, Lucky; Mudita, Mudita; Najuah, Najuah; Refranisa, Refranisa; Mihadi Putra, Yananto; Hidayah, Nurul (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2025)
The problem of waste management in Ciputri Village triggers environmental pollution and low community welfare due to the lack of awareness of sorting waste from the source and the weak institution of waste banks. This Community Service activity aims to increase the technical and managerial capacity of The Youth Organization (Karang Taruna) as a driver of empowerment-based waste bank management. The approaches carried out include institutional assistance, technical training in waste sorting and processing, continuous education, and implementing an incentive-based waste savings system. The results of the activities showed a significant increase in community participation, management skills, and the effectiveness of waste bank management, including the formation of a clear organizational structure and SOPs. This program reduces landfill waste, increases residents' income, and strengthens recycling networks. The program's sustainability is recommended through follow-up mentoring, diversification of recycled products, and multi-stakeholder collaboration.